Comparison of three different assessments of capacity to consent in dementia patients - Müller, Tanja; Knebel, Maren; Schröder, Johannes (GeroPsych, 2015)
We compared clinical assessments of capacity to consent to medical treatment with results obtained using the MacArthur Competence Tool for Treatment (MacCAT-T). Capacity to consent to treatment wit...
Gesehen am 20.07.2020